Photoluminescence: Thermally Activated Upconversion Near‐Infrared Photoluminescence from Carbon Dots Synthesized via Microwave Assisted Exfoliation (Small 50/2019). Issue 50 (13th December 2019) - Li, Di; Liang, Chao; Ushakova, Elena V.; Sun, Minghong; Huang, Xiaodan; Zhang, Xiaoyu; Jing, Pengtao; Yoo, Seung Jo; Kim, Jin‐Gyu; Liu, Enshan; Zhang, Wei; Jing, Lihong; et al.
Abstract : Near‐infrared (NIR) emissive materials are highly attractive for fluorescence bio‐imaging application. In article number 1905050, Songnan Qu and co‐workers develop NIR absorbing/emissive carbon dots via microwave assisted exfoliation. More importantly, a unique thermally activated up‐conversion NIR emission is observed under 808 nm continuous‐wave laser excitation.